Hubad - Celiz, Rey Natalbo
"In a society where people are still governed by mores and norms, non-confirmists are almost often ostracized, scoffed at or underestimated. This is true especially when it involves a question of one's occupation. What if your job is macho dancing? In the Philippines, macho dancing is till considered a scandalous and an ignoble job. People always equate macho dancing with prostitution. There is a grain of truth to this generalization because macho dancing has always been associated with "easy money" in return for voyeuristic and/or sexual favors. It is a work that requires only an Adonis-like physique and visage and certain boldness from the dancer to seduce and strip in front of an exclusive audience willing to shell out wads of bills for a moment's gratification. Macho dancing is thus a less popular yet a monetarily rewarding career option for young, poor and undereducated men. Notwithstanding this predicament, there are isolated cases of males who enter the job to satisfy their narcissistic proclivities. They work as macho dancers to be admired by people and in the process, worshipped for their handsome features. Narcissim, then, can be a motivating factor for some to work as macho dancers."